2016
DOI: 10.1177/2233865915626832
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability, livelihoods and social inequities: The vulnerability of migrant workers in Indian cities

Abstract: This paper examines the vulnerability context of migrant workers in the informal sector in three Indian cities (Kochi, Surat and Mumbai), specifically in terms of how their livelihoods interface with climate variability, related hazard events and social inequities. It examines the progression of population vulnerability from a political economy perspective. The underlying assumption is that migrant workers' vulnerability to climate variability in cities is closely embedded within the wider political economy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Social marginalisation and exclusion of ‘lower’ castes in the rural areas therefore often prevent people's development and progress. For example, people of ‘lower-castes’ are restricted access to resources and institutions which turn into a vicious inescapable circle of poverty (Bosher, Penning-rowsell and Tapsell, 2007; [ 62 ]). Adding to this, people on the move tend to lack access to affordable and stable health care services, and often live in unsafe conditions that increases their vulnerability to health risks ([ 28 ]; Ayeb-Karlsson, Kniveton and Cannon[ 49 ]).…”
Section: The Plight Of Migrant Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Social marginalisation and exclusion of ‘lower’ castes in the rural areas therefore often prevent people's development and progress. For example, people of ‘lower-castes’ are restricted access to resources and institutions which turn into a vicious inescapable circle of poverty (Bosher, Penning-rowsell and Tapsell, 2007; [ 62 ]). Adding to this, people on the move tend to lack access to affordable and stable health care services, and often live in unsafe conditions that increases their vulnerability to health risks ([ 28 ]; Ayeb-Karlsson, Kniveton and Cannon[ 49 ]).…”
Section: The Plight Of Migrant Workersmentioning
confidence: 99%
“…Adding to this, people on the move tend to lack access to affordable and stable health care services, and often live in unsafe conditions that increases their vulnerability to health risks ([ 28 ]; Ayeb-Karlsson, Kniveton and Cannon[ 49 ]). Similarly to the characteristics of slum settings, these living and working conditions can be catastrophic for the spread of infectious diseases [ 62 ].…”
Section: The Plight Of Migrant Workersmentioning
confidence: 99%
“…For instance, around 95 per cent of weaving businesses reported that a proportion of their employees had migrated from the city of Surat immediately after the flood; some of them could have temporarily out-migrated and returned once the situation had normalized, but others might not have returned to Surat. Similarly, flood-induced displacement is a serious issue, especially for migrants (Santha et al, 2015). This could be the major factor determining how long these businesses took to resume normal production, and also have indirectly impacted on the family members of the migrant workers, if remittances were the major source of income.…”
Section: Economic and Non-economic Loss And Damages Of Textile Businementioning
confidence: 99%
“…4 Studies indicate a high incidence of fungal and bacterial skin diseases among these migrants owing to poor personal hygiene. 5 The high incidence of skin diseases among this category due to lack of basic amenities and lack of awareness about the possible health problems that could arise from such unhealthy living environments. Our study aimed to assess the prevalence of skin diseases and provide epidemiological data regarding various dermatoses among migrant workers in Puducherry.…”
Section: Introductionmentioning
confidence: 99%